SENSORY CHARACTERISTICS AND CHEMICAL PROPERTIES OF COFFEE LEAF TEA (Coffea sp) AS A FUNCTIONAL BEVERAGES - Andi Abriana; Saiman Sutanto; Andi Tenri Fitriyah; Aylee Christine Alamsyah Sheyoputri; Ahmad Muktafi Hadi; Khairunnisa Khairunnisa (Jurnal Industri Hasil Perkebunan, 2023)
: Coffee leaves can be processed into functional beverages because they have a fairly high tannin content and a taste that is no less delicious than coffee beans so that they can be used as a substitute for tea leaves in the processing of coffee leaf tea. Red ginger can be added to coffee leaf tea because it is beneficial for health as an antioxidant and can increase endurance.  This study aims to: (1) Examine the effect of the concentration of coffee leaf comparison with red ginger on coffee leaf tea processing and (2) Examine the sensory characteristics of coffee leaf tea with the addition of red ginger. The research treatment was coffee leaves with concentrations (100%, 70%, 60%, 50%) and red ginger powder with concentrations (0%, 30%, 40%, 50%). Data analysis using a Complete Randomized Design (RAL), with four treatment levels and three repeats. The results of study obtained the best treatment with a ratio of coffee leaves 50%: red ginger 50% in terms of aroma 3.87 (likes), color 3.31 (likes), flavors without sugar 3.08 (likes), flavors of sugar addition 3.93 (likes), water content 3.46%, and ash content 5.26 %, The water content, ash content and color of coffee leaf tea with the addition of red ginger produced in this study meet SNI 03-3836-2012.